In vivo imaging of intraocular fluidics in vitrectomized swine eyes using a digital fluoroscopy System - Tandogan, Tamer; Khoramnia, Ramin; Auffarth, Gerd U.; Koss, Michael Janusz; Choi, Chul Y. (Journal of ophthalmology, 2016)
Purpose. To describe the characteristics of intraocular fluidics during cataract surgery in swine eyes with prior vitrectomy. Methods. We prepared three groups of enucleated swine eyes (nonvitrectomized, core, and totally vitrectomized). Irrigation and aspiration were performed (2.7 mm conventional sleeved phacosystem) using a balanced saline solution mixed with a water-soluble radiopaque contrast medium at 1 : 1 ratio. We imaged the eyes using a digital fluoroscopy system (DFS) during phacoemulsification and compared the characteristics of the intraocular fluid dynamics between the groups. Results. The anterior chamber depth (ACD) after the commencement of irrigation differed between groups ( mm; mm; mm), as well as the height of the fluid flowing from the anterior chamber into the posterior cavity that was identified by lifting up the iris to correct the infusion deviation syndrome ( mm; mm; mm). Conclusions. DFS demonstrated differences in fluid dynamics during phacoemulsification in swine eyes with or without prior vitrectomy. In completely vitrectomized eyes, the large ACD, which developed during phacoemulsification, could be reduced by lifting the iris and allowing the fluid to shift to the posterior cavity. Recognizing the differences in fluidics of vitrectomized eyes as compared to those of the nonvitrectomized eyes may reduce the frequency of intraoperative complications.
Gesehen am 02.06.2020